Peningkatan Pemahaman Materi Jaring-Jaring Kubus dan Balok Melalui Kerja Kelompok pada Siswa Kelas V SD - Pipit Saraswati Indriasari; Ahmad Fathoni; Minsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: Improving the Understanding of the Material of Nets of Cubes and Blocks through Group Work in Grade V Elementary School Students. This study aims to determine the application of the group work learning model in improving the understanding of the concept of cube and block jarrings in grade V elementary school students. This research is a class action research. The method used in this study is the Classroom Action Reseach method. This research is carried out through two cycles, each cycle consists of four stages, namely, planning, action, observation, and reflection. Cycle I there was an increase in understanding of the concept of cube and block space construct nets from a pre-cycle average of 64.8 to 74.7 and from the achievement of the Minimum Completion Criteria (KKM) of 33.3% to 66.7%. Cycle II saw an increase in understanding of the concept of cube and beam space construct nets from a cycle I average of 74.7 to 81.6 and from a KKM achievement of 66.7% to 100%. The results showed that mathematics learning through group work learning can improve understanding of the concept of building space in the material of cube and block nets in grade V elementary school students.